2003
DOI: 10.1097/01.brs.0000058932.73728.a8
|View full text |Cite
|
Sign up to set email alerts
|

Radical Excision in the Management of Thoracic and Cervicothoracic Tumors Involving the Spine: Results in a Series of 36 Cases

Abstract: Even though a learning curve is necessary to achieve this extreme type of surgery, selective preoperative screening of patients is mandatory. Interesting results today confirm the feasibility of possible treatment of tumors still considered unresectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The Second Affiliated Hospital of Xi'an Jiaotong University Medical School has successfully treated a number of cases of total spondylectomy with satisfactory results. Different techniques for en bloc resection have previously been described (8)(9)(10)(19)(20)(21). To achieve a total spondylectomy and reconstruction, a combined anterior-posterior surgical approach has usually been used.…”
Section: Discussionmentioning
confidence: 99%
“…The Second Affiliated Hospital of Xi'an Jiaotong University Medical School has successfully treated a number of cases of total spondylectomy with satisfactory results. Different techniques for en bloc resection have previously been described (8)(9)(10)(19)(20)(21). To achieve a total spondylectomy and reconstruction, a combined anterior-posterior surgical approach has usually been used.…”
Section: Discussionmentioning
confidence: 99%
“…The main pattern of recurrence is that of distant metastases, especially in the brain. Invasion of the vertebral column is not a contraindication for surgery which should be made en bloc with pulmonary parenchyma resection [5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Sundaresan et al [49] reported a mean survival time of 30 months in patients with surgery for solitary metastases of the spine and with a survival of 5 years and more in 18% of their cases. Mazel et al [42] achieved a mean survival rate of 16.7 months in 21 of 35 patients who died and 38.2 months in 14 of 35 patients who were alive at follow-up with a so-called radical excision of tumors of thoracic and cervicothoracic metastases. These results also suggest a concept of differentiated surgery with more radical options than just palliative surgery.…”
Section: Pharmacological Optionsmentioning
confidence: 99%
“…Again, with modern retractor systems and less invasive technology it is possible to perfect the posterolateral approach to the anterior spine elements of the thoracolumbar spine through a midline incision which allows a laminectomy, a vertebral body resection, the anterior column reconstruction and posterior stabilization in a single approach (Fig. 5) [41,42]. In the middle and lower cervical spine the anterior approach is most straightforward and yields little morbidity (Fig.…”
Section: Surgical Optionsmentioning
confidence: 99%
See 1 more Smart Citation